The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1099/vir.0.80148-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification and characterization of two proposed new enterovirus serotypes, EV74 and EV75

Abstract: Sequencing of the gene that encodes the capsid protein VP1 has been used as a surrogate for antigenic typing in order to distinguish enterovirus serotypes; three new serotypes were identified recently by this method. In this study, 14 enterovirus isolates from six countries were characterized as members of two new types within the species Human enterovirus B, based on sequencing of the complete capsid-encoding (P1) region. Isolates within each of these two types differed significantly from one another and from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
87
0
4

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 105 publications
(93 citation statements)
references
References 30 publications
2
87
0
4
Order By: Relevance
“…Non-Polio enteroviruses (NPEV), Picornaviridae family, are responsible for over 80% of viral meningitis in which the etiologic agent is identified [Morens and Pallansch, 1995]. Human enteroviruses (EV) are constituted by the following viral serotypes: Poliovirus (3 serotypes), Coxsackievirus A (23 serotypes), Coxsackievirus B (6 serotypes), Echovirus (28 serotypes), and other Enterovirus recently classified (Enteroviruses serotypes 68-71, 73-78, 89-91) [Pringle, 1999;King et al, 2000;Oberste et al, 2001Oberste et al, , 2004Oberste et al, , 2005Norder et al, 2003].…”
Section: Introductionmentioning
confidence: 99%
“…Non-Polio enteroviruses (NPEV), Picornaviridae family, are responsible for over 80% of viral meningitis in which the etiologic agent is identified [Morens and Pallansch, 1995]. Human enteroviruses (EV) are constituted by the following viral serotypes: Poliovirus (3 serotypes), Coxsackievirus A (23 serotypes), Coxsackievirus B (6 serotypes), Echovirus (28 serotypes), and other Enterovirus recently classified (Enteroviruses serotypes 68-71, 73-78, 89-91) [Pringle, 1999;King et al, 2000;Oberste et al, 2001Oberste et al, , 2004Oberste et al, , 2005Norder et al, 2003].…”
Section: Introductionmentioning
confidence: 99%
“…EV71 and CVA16 belong to Human enterovirus A. VP1 sequences correlate well with antigenic typing by neutralization, and can be used for virus identification and evolutionary studies (Oberste et al, , 2004 RT-PCR for 5 §UTR and VP1. Reverse transcription was performed as described previously .…”
Section: Introductionmentioning
confidence: 99%
“…Molecular typing methods depend largely on RT-PCR amplification and nucleotide sequencing of the entire or 39 half of the VP1 gene (Pallansch & Roos, 2007). Comparison of individual VP1 sequences with databases of VP1 sequences of HEV prototype and variant strains allows genotype assignment and identification of new enteroviruses (Oberste et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that enteroviruses should be classified in the same serotype if they have >75 % nucleotide similarity in the VP1-coding sequence (>85 % amino acid sequence similarity) and into different serotypes if they have <70 % nucleotide similarity (<85 % amino acid similarity). Molecular typing of serologically nontypable strains has led to the discovery of a large number of new enterovirus types (Oberste et al, 2001(Oberste et al, , 2004c(Oberste et al, , 2005 Norder et al, 2003).Detection of circulating wild-type poliovirus strains has become more and more important as the World Health Organization (WHO)-coordinated global poliomyelitis eradication initiative is approaching its goal (Hovi, 2006). Poliomyelitis typically presents itself as a rapidly progressing, usually unilateral AFP, often with fever and residual paralysis at day 60 after onset.…”
mentioning
confidence: 99%